Pericardiectomy for Pleuropericardial Effusion Complicating Bacterial Pneumonia. (30th May 2010) - Quarti, Andrea; de Benedictis, Fernando Maria; Soura, Elli; Pozzi, Marco
Abstract : Severe pericardial effusion is a rare complication of bacterial pneumonia and it usually disappears under medical treatment. Herein we report a case of a girl with a congenital immunodeficient syndrome and bacterial pneumonia, who developed recurrent and life-threatening pericardial effusion refractory to medical treatment. She was finally treated with pericardiectomy.